Financial Feasibility Analysis of Wooden Fishing Vessel in Panggungrejo Subdistrict, Pasuruan, East Java - Sri Rejeki Wahyu Pribadi; Rizky Chandra Ariesta; Hutami Putri Puspitasari (Faculty of Fisheries and Marine Science, Brawijaya University, 2019)
Fishermen in fishing to catch fish need tools to get fish. The tools used here are fishing vessels. livelihoods as fishermen are carried out from generation to generation, the demand for fishing boat production will increase. Pasuruan is one of the producing areas of wooden ships with good quality and able to compete, with this potential it is necessary to analyze the financial feasibility of wooden boatyards in Pasuruan which will produce NPV, IRR, BC ration and timber boat dock payback periods in Pasuruan in a row amounted to IDR 505,472,000, 59%, 3.46 and 1.89 per year. The results obtained over the eligibility criteria of the financial value of NPV >1 and BC ratio > 1, so the wooden boatyard business in Pasuruan fulfills the feasibility value index to continue and development.